Modular synthesis of polyene side chain analogues of the potent macrolide antibiotic etnangien by a flexible coupling strategy based on hetero-bis-metallated alkenes - Altendorfer, Mario (Organic & biomolecular chemistry, 2013)
An efficient procedure for the concise synthesis of hetero-bis-metallated alkenes as useful building blocks for the modular access to highly elaborate polyenes and stabilized analogues is reported. By applying these bifunctional olefins in convergent Stille/Suzuki-Miyaura couplings, novel, carefully selected side chain analogues of the potent RNA polymerase inhibitor etnangien were synthesized by a modular late stage coupling strategy and evaluated for antibacterial and antiproliferative activities.